الاصلاحات الجديدة للمنظومة التربوية و اثرها على التحصيل الدراسي دراسة حالة لعينة من اساتذة ثانويات ولاية الاغواط - بن جدو عبد الغني; موسى خويلد (My University, 2023)
Our study was entitled: New reforms of the educational system and their impact on academic achievement A case study of a sample of high school teachers in the state of Laghouat. Our study began with the problem: What is the extent of the impact of the new educational reforms on the academic achievement of students? Through our study in general, we aimed to identify new educational reforms. The descriptive approach was relied upon in our study. In order to reach the field results, we relied on 60 individuals from the research community. We relied on the questionnaire data collection tool and after analyzing it, we reached the following results: -Educational reforms in Algeria that Algeria has undertaken in the education sector, working to create a suitable atmosphere for school work between the student and the teacher. -All the reforms undertaken by the Algerian state in the field of the education sector since 2003 until the present day have not achieved the goals aimed at finding solutions to the problems of the education sector. Teachers believe that the educational reforms that the Algerian state has worked on in the education sector have achieved all the goals for which they were programmed and did not embody all the ambitions. -Educational reforms, the principles of which include giving value to the teacher and the student, by working to create an appropriate atmosphere for school work between the student and the teacher. Today we live in the era of technology with all its means, which has facilitated much of life. Therefore, the education sector was one of the areas that dominated it, and thus relying on technology in teaching motivates the student and keeps him away from boredom. -Educational reforms did not find a solution to the pedagogical work that has become burdensome on the shoulders of the professor in educational institutions that know the limited time for work and the large number of programs. Keywords: educational reform - academic achievement